Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Climate snow-avalanche linkage revealed by geomorphological, historical and tree-ring records in the central Spanish Pyrenees - Osvaldo Franco-Ramos; Jaime Boyano-Galiano; Alberto Muñoz-Torrero Manchado; Juan Ignacio López-Moreno; Juan Antonio Ballesteros-Cánovas (Cold Regions Science and Technology, 2026)

Using banana peels in fermentation: upstream bioprocesses - Mariana C. Pedrosa; Sandrina A. Heleno; Ana Susmozas; Paloma Manzanares; Ignacio Ballesteros; Manuela Pintado; Lillian Barros; Marcio Carocho (Phytochemistry Letters, 2025)

Rockfall-induced debris flow event in the Pyrenees: The case of Pineta valley of September 2022 - Juan A. Ballesteros-Cánovas; Ishel Marsal Twose; Alberto Muñoz-Torrero; José Carlos Robredo Sánchez; Tamir Grodek; Ignacio López-Moreno; Miguel Bartolomé; Gerardo Benito (CATENA, 2025)

Distribution and morphological differentiation of native alder taxa (Alnus Mill.) in the Iberian Peninsula - Macarena Cuerdo; José Ignacio Márquez-Corro; Francisco Lara; Ricardo Garilleti; Ilia J. Leitch; Eduardo Cires; David G. del Olmo; Alba Romero; Carmen Andrés; Eduardo Ballesteros; Álvaro Prado; Juan A. Calleja (Flora, 2025)

Green solvents extraction-based detoxification to enhance the enzymatic hydrolysis of steam-exploded lignocellulosic biomass and recover bioactive compounds - Raquel Cañadas; Raquel Martín-Sampedro; María González-Miquel; Emilio J. González; Ignacio Ballesteros; María E. Eugenio; David Ibarra (Journal of Environmental Management, 2023)

Assessing the expansion and success of a restored population of Gongolaria barbata (Stackhouse) Kuntze (Fucales, Phaeophyceae) using high-precision positioning tools and size distribution frequencies - ALICIA GRAN; JUANCHO MOVILLA; ENRIC BALLESTEROS; MARTA SALES; IGNACIO BOLADO; CRISTINA GALOBART; MARIA ELENA CEFALÌ (Mediterranean Marine Science, 2022)
Ongoing human pressures over recent decades have caused the loss and ensuing impoverishment of the complexity and diversity of Mediterranean habitats dominated by algal species of the order Fucales. Gongolaria barbata, a habitat-forming Fucales species that has disappeared in several places across the Mediterranean, was reintroduced in a cove (Cala Teulera, Maó Bay, Menorca) where it was known to have been locally extinct for more than 40 years. Reintroduction was performed in 2011 using innovative non-destructive techniques. Here we describe the expansion patterns of the population ten years after its reintroduction, and we look at the size-structure distribution of the restored population compared to one of the only natural populations known in Spain (Fornells Bay, Menorca). Newly settled individuals exhibit a progressive dispersal pattern from restoration sites, favouring rocky substrates at the shallowest level parallel to the shore. The area occupied by G. barbata has increased by almost three orders of magnitude in ten years, from approximately 3.6 m2 of the initially restored area to a current restored area of 2093 m2. Recruits and juveniles dominate the restored population but some individuals have reached large size classes, the overall size distribution resembling the reference population. The high-resolution cartography included in our study enables an accurate mid to long-term assessment of the expansion of G. barbata. Incorporating such tools in restored marine forests would facilitate the implementation of efficient management policies that will help reinforce their conservation

Vineyard yield estimation by combining remote sensing, computer vision and artificial neural network techniques - Rocío Ballesteros; Diego S. Intrigliolo; José F. Ortega; Juan M. Ramírez-Cuesta; Ignacio Buesa; Miguel A. Moreno (Precision Agriculture, 2020)

Effect of microalgae storage conditions on methane yields - Santiago Barreiro-Vescovo; Ignacio de Godos; Elia Tomás-Pejó; Mercedes Ballesteros; Cristina González-Fernández (Environmental Science and Pollution Research, 2018)

Using electrical resistivity tomography to assess the effectiveness of managed aquifer recharge in a salinized coastal aquifer - Olga García-Menéndez; Bruno J. Ballesteros; Arianna Renau-Pruñonosa; Ignacio Morell; Tania Mochales; Pedro I. Ibarra; Félix M. Rubio (Environmental Monitoring and Assessment, 2018)

A Standardized Index for Assessing Seawater Intrusion in Coastal Aquifers: The SITE Index - Bruno J. Ballesteros; Ignacio Morell; Olga García-Menéndez; Arianna Renau-Pruñonosa (Water Resources Management, 2016)

Physical activity affects plasma coenzyme Q10 levels differently in young and old humans - Jesús Del Pozo-Cruz; Elisabet Rodríguez-Bies; Manuel Ballesteros-Simarro; Ignacio Navas-Enamorado; Bui Thanh Tung; Plácido Navas; Guillermo López-Lluch (Biogerontology, 2014)